PERAN GURU DALAM PENDAMPINGAN PESERTA DIDIK UNTUK MEWUJUDKAN SEKOLAH BEBAS BULLYING DI SD SWASTA ISLAM QURRATU A’YUN DELI TUA - Lince Tomotia Sianturi; Taufiqurrahman Surbakti (Smart Education, 2025)
Abstract: This research is motivated by the phenomenon of bullying that has long occurred in the school environment and teachers as professionals in the field of education have the responsibility to create a safe and violence-free school environment. The purpose of this study is to explore the role of teachers in assisting students to prevent bullying at the Qurratu A'yun Islamic Private Elementary School and explain teacher strategies in preventing bullying at the Qurratu A'yun Islamic Private Elementary School. This type of research is descriptive qualitative research. This study uses a purposive sampling technique to determine the research sample. The sample of this study is a class teacher at an elementary school in Deli Serdang. The data collection technique used is interviews. Data analysis techniques include data reduction, data presentation, drawing conclusions and verification. The results of the study show (1) the role of teachers in assisting students to prevent bullying at the Qurratu A'yun Islamic Private Elementary School is as a supervisor and detector of early signs of bullying, as a guide and director, as a mediator or bring together, and as an advisor. Keyword: Role of Teachers, Mentoring, Prevention, Bullying Abstrak: Penelitian ini dilator belakangi oleh fenomena bullying yang telah lama terjadi di lingkungan sekolah dan guru sebagai profesional dalam bidang pendidikan memiliki tanggung jawab untuk menciptakan lingkungan sekolah yang aman dan bebas dari kekerasan. Tujuan penelitian ini adalah untuk mengeksplor peran guru dalam pendampingan peserta didik untuk mencegah bullying di SD Swasta Islam Qurratu A’yun dan menjelaskan strategi guru dalam mencegah bullying di SD Swasta Islam Qurratu A’yun. Jenis penelitian ini adalah penelitian kualitatif yang bersifat deskriptif. Penelitian ini menggunakan teknik purposive sampling untukmenentukan sampel penelitian. Sampel penelitian ini adalah guru kelas di salah satu Sekolah Dasar di Deli Serdang. Teknik pengumpulan data yang digunakan ialah wawancara. Teknik analisis data antara lain reduksi data, penyajian data, penarikan kesimpulan dan verifikasi. Hasil penelitian menunjukkan (1) peran guru dalam pendampingan peserta didik untuk mencegah tindakan bullying di SD Swasta Islam Qurratu A’yun adalah sebagai pengawas dan pendeteksi tanda-tanda awal bullying, sebagai pembimbing dan pengarah, sebagai mediator atau mempertemukan, serta sebagai penasihat. Kata Kunci: Peran Guru, Pendampingan, Pencegahan, Bullying